Determinant of roles of personal representative in administration of estates in Malaysia and its challenges - Drs Nasrul, Muhammad Amrullah; Mohd Salim, Wan Noraini; Halim, Akmal Hidayah; Abdul Hak, Nora (2018)
Administration of estate refers to a process of managing and distributing the deceased’s estate to the beneficiaries which take effect after his death. The tasks to administer the estate are handled by the personal representative from the beginning until the end of the administration. Appointment of capable personal representative is therefore important as administration of estate deals with various responsibilities and different complications throughout the entire process. This article heeds on the notion that the appointment of incompetent personal representative disrupts the process in the administration of estate that leads to adverse implications, including the misappropriation and delay in distribution of asset. This paper discusses on the roles and duties of the personal representative and the comparison between individual and institution assigned as the personal representative. This paper also highlights the challenges encountered by the personal representative in managing the estate of the deceased. As part of its research method, this qualitative legal study undertakes a library based study through the analysis of selected materials including journal articles, textbooks, statutes and cases. The findings from this writing indicate that ignorance of the roles and lack of deliberation in appointing personal representative serve as factors leading to adverse management which often results in incompletion of the administration. The insights from this paper contribute to the public in instilling the awareness as to the importance of personal representative in estate administration. It also contribute to the academic section as part of the integral knowledge under the law of inheritance.